Effect of Packaging on Microbial Quality of Edible Flowers During Refrigerated Storage - Aleksandra Wilczyńska; Anita Kukułowicz; Anna Lewandowska (Polish Journal of Food and Nutrition Sciences)
Edible flowers are food products that are usually eaten fresh without prior heat treatment. Due to their chemical composition and low degree of processing, they can be an excellent breeding ground for microorganisms, and thus a source of infection. Methods of their preservation include proper packaging and storage at low temperatures. Therefore the aim of this study was to evaluate the effect of type of packaging (vacuum-sealed polyamide/polyethylene bag and polyethylene terephthalate box) on the microbial contamination of edible flowers including nasturtium, calendula, and daisy during refrigerated storage. The counts of selected pathogenic bacteria, total yeasts and moulds on the day of harvesting and after 1–3 days of refrigerated storage were determined. The results showed that the edible flowers did not contain Salmonella sp. or Escherichia coli (except nasturtiums), while all flowers contained both yeast and moulds at counts about 4–5 log cfu/g, and Staphylococcus aureus at numbers ranging from 1.89 to 2.72 log cfu/g. The differences in the counts of moulds and S. aureus were statistically significant depending on the type of flower. Neither the type of packaging nor storage time under refrigerated conditions influenced the degree of microbial contamination of the flowers.